INVESTIGATION OF THE ANTIBACTERIAL EFFICACY OF DERSONO WATER APPLE LEAVES (SYZYGIUM MALACCENSE) AS A SUBSTITUTE THERAPY FOR STREPTOCOCCUS PYOGENES INFECTIONS - Devi Usdiana Rosyidah; Nur Mahmudah; Sa’idatul Fithriyah; Retno Sintowati (Universitas Muhammadiyah Surakarta, 2025)
Streptococcus pyogenes caused different illnesses, including pharyngitis and dermatological infections. The Dersono water apple leavesSyzygium malaccense) are recognized for their bioactive ingredients, which may serve as antibacterial agents. This study purpose was to determine the antibacterial potential of ethanol extract and acetone fraction of Syzygium malaccense against Streptococcus pyogenes infection. This research was a laboratory xperiment, a post-test only with control group design. Assessing growth inhibition by measuring the diameter of halo around the well of blood agar plate. Statistical tests using the Sapiro-Wilk test, Lavene test, Kruskal Wallis est and Mann-Whitney test. The study's findings demonstrated that the ethanol extract 25% (11.80 mm) and 50% (16.51) concentrations and acetone fraction of Dersono water apple leaves, at 25% (11.25 mm) and 50% (12.08) concentrations, had strong inhibitory power. The concentrations of 6.25% (8.15 mm) and 12.50% (9.63 mm), the ethanol extract's inhibitory power was superior than the concentrations of 6.25% (4.42 mm) and 12.50% (3.38 mm) acetone fraction, had moderate range. Both the ethanol extract and the acetone fraction's phytochemical analyses identified alkaloids, tannins, and saponins. The conclusion was ethanol extract and acetate fraction of Dersono water apple leaves have antibacterial effects against Streptococcus pyogenes.